Electron–Phonon Coupling and Electron–Phonon Scattering in SrVO3. Issue 15 (19th June 2021) - Mirjolet, Mathieu; Rivadulla, Francisco; Marsik, Premysl; Borisov, Vladislav; Valentí, Roser; Fontcuberta, Josep
Abstract: Understanding the physics of strongly correlated electronic systems has been a central issue in condensed matter physics for decades. In transition metal oxides, strong correlations characteristic of narrow d bands are at the origin of remarkable properties such as the opening of Mott gap, enhanced effective mass, and anomalous vibronic coupling, to mention a few. SrVO3 with V 4+  in a 3d 1  electronic configuration is the simplest example of a 3D correlated metallic electronic system. Here, the authors' focus on the observation of a (roughly) quadratic temperature dependence of the inverse electron mobility of this seemingly simple system, which is an intriguing property shared by other metallic oxides. The systematic analysis of electronic transport in SrVO3  thin films discloses the limitations of the simplest picture of e–e correlations in a Fermi liquid (FL); instead, it is shown show that the quasi‐2D topology of the Fermi surface (FS) and a strong electron–phonon coupling, contributing to dress carriers with a phonon cloud, play a pivotal role on the reported electron spectroscopic, optical, thermodynamic, and transport data. The picture that emerges is not restricted to SrVO3  but can be shared with other 3d and 4d metallic oxides. Abstract : The strong coupling between free electrons and the lattice in ionic materials leads to the formation of polarons. In early transition metal oxides, the Fermi surface has a cylindrical shape that limits the phonons available for scattering. In SrVO3  and related Fermi liquids, both mechanisms can contribute to the ubiquitously observed quasi‐ T 2  temperature dependence of the electrical resistivity.